Sports Cardiology - Schüttler D; 2; 3; Hamm W; 2; Bauer A; 4; Brunner S (Deutsche Zeitschrift für Sportmedizin)
In the last years biomarkers of the autonomic nervous system have been increasingly used in sports medicine to optimize guidance of training intensity and detect training-induced fatigue. Especially heart rate-based biomarkers, including heart rate variability (HRV) and heart rate recovery (HRR) have been tested extensively in these fields for many years. Recently, novel ECG-based biomarkers deceleration capacity (DC) and periodic repolarization dynamics (PRD) have been established and hold promise for future sports research. These markers reflect influences of sympathetic and vagal nervous systems and can be modulated by external and internal factors such as stress, sports, hypobaric/hypoxic states athigh altitude or under hyperbaric conditions while diving. Furthermore, these markers are used for risk stratification of sudden cardiac death (SCD) in cardiovascular patients.In this review we briefly highlight these autonomic biomarkers in sports performance diagnostics and high altitude medicine as well as diving and illustrate their role as predictors of SCD. Due to the extent of the review we focus on the most established and promising parameters:heart rate variability (HRV), heart rate recovery (HRR), periodic repolarization dynamics (PRD) and deceleration capacity (DC). We aim to provide an overview of their current and potential application in sports medicine and discusscurrent challenges in interpretation. KEY WORDS: Periodic Repolarization Dynamics, Deceleration Capacity, Training Control, Risk Stratification, Sudden Cardiac Death, Heart Rate Variability